Preparation method and application of electrochemical polymeric material of lithium ion battery cathode
The hydrophilic diaminonaphthalene is improved through electrochemical polymerization technology to form poly-hydrophilic diaminonaphthalene materials, solving the problems of low redox stability and conductivity of the cathode materials of lithium-ion batteries and achieving higher battery performance.
Patent Information
- Application Number
- CN202411834725.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-28
AI Technical Summary
The low redox stability of existing lithium-ion battery cathode materials, high solubility in electrolytes, and low conductivity limit their application performance.
Through electrochemical polymerization, hydrophilic diaminonaphthalene (HAHQS) is improved to form poly-hydrophilic diaminonaphthalene (P-HAHQS) materials, increasing the layer spacing of active sites and molecular structures.
The specific capacity, rate capability, cycle stability and Coulomb efficiency of lithium-ion batteries are improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a preparation method and application of an electrochemical polymer material for a lithium ion battery cathode. Background Art
[0002] With the rapid development of society, new energy vehicles emerge in an endless stream, and people's demand for lithium-ion batteries is increasing; therefore, while paying attention to battery performance, people pay more attention to reducing costs. At present, due to the advantages of low cost, high abundance, environmental friendliness, high theoretical capacity, good structural versatility and flexibility of organic electrode polymer materials, lithium-ion batteries are once again interested in organic electrode polymer materials. Despite the above advantages, low redox stability, high solubility in electrolytes and low conductivity are still the key limitations of these polymer materials in the cathode of lithium-ion batteries.
[0003] At present, a common strategy to solve the solubility problem of cathode materials is to use organic polymer materials. Embedding redox active sites in porous organic frameworks can improve the diffusion of ions, while porous organic conjugated frameworks can increase the diffusion rate of ions and electronic conductivity. Therefore, the present invention designs and modifies the corresponding molecular framework of organic materials by electropolymerization, so that the assembled lithium-ion battery obtains higher specific capacity, excellent rate capability, long-term cycle stability and nearly uniform coulombic efficiency.
[0004] Therefore, we disclose a preparation method and application of an electrochemical polymer material for a lithium ion battery cathode. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method and application of an electrochemical polymer material for a lithium ion battery cathode to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing an electrochemical polymer material for a lithium ion battery cathode comprises the following steps: Step 1: Add diaminonaphthalene to concentrated nitric acid, mix evenly, heat in an oil bath at high temperature, filter, wash and dry to obtain hydrophilic diaminonaphthalene; Step 2: Evenly mix hydrophilic diaminonaphthalene, polytetrafluoroethylene and pure water, add isopropanol, stir and grind evenly, and dry to obtain a hydrophilic diaminonaphthalene electrode material; Step 3: subjecting the hydrophilic diaminonaphthalene electrode material to an electropolymerization reaction to obtain an electrochemical polymer material.
[0007] Preferably, in step 3, the parameters of the electropolymerization reaction are set as follows: the charging voltage is set to 0.6-1 V vs. Ag / AgCl, and the current density is set to 0.1-0.5 A g -1 The electropolymerization reaction time is 1 to 4 hours; the electrochemical polymerization material is a poly-hydrophilic diaminonaphthalene material.
[0008] In the scheme, the present invention successfully improved the hydrophilic diaminonaphthalene (HAHQS) by electrochemical polymerization based on the self-polymerization mode: by applying a certain potential or current, the monomer undergoes oxidation or reduction reaction on the electrode surface or in the solution, thereby generating active intermediates such as free radicals or ions, which further interact with each other to form polymer chains.
[0009] More optimally, in step 2, the mass ratio of the hydrophilic diaminonaphthalene (HAHQS) to polytetrafluoroethylene is (9-9.5):(0.5-1); the drying temperature is 60-65°C, and the drying time is 20-24 hours.
[0010] More optimally, in step 1, the concentration of the concentrated nitric acid is 7.5-8 mol / L; the amount of concentrated nitric acid and pure water used for filtering and washing is 30 times the mass of diaminonaphthalene (AHQS).
[0011] More optimally, in step 1, the oil bath heating temperature is 120-140° C., and the oil bath heating time is 12-20 hours; the drying temperature is 80° C., and the drying time is 12-24 hours.
[0012] A method for preparing an electrochemical polymer material for a lithium ion battery cathode and application of the obtained electrochemical polymer material in a lithium ion battery.
[0013] A more optimized method for applying the electrochemical polymer material in a lithium-ion battery is: Step S1: uniformly mixing poly-hydrophilic diaminonaphthalene material (P-HAHQS), carbon black, polyvinylidene fluoride (PVDF), and N-methyl-2-pyrrolidone (NMP) to prepare a cathode slurry; Step S2: coating the cathode slurry on aluminum foil and drying it, and then rolling, die-cutting, slitting, welding the tabs, and encapsulating it to obtain cathode pole pieces; cutting the lithium sheets into anode pole pieces; Step S3: The cathode electrode and the anode electrode are separated by a polyethylene porous membrane, and the electrolyte is a mixed solution of lithium hexafluorophosphate and lithium trifluoromethanesulfonate; the three layers are pressed between two collectors, one of which is in contact with the cathode electrode and the other is in contact with the anode electrode; the entire lithium-ion battery is placed in a glove box filled with argon and finally assembled into a lithium-ion battery.
[0014] In a more optimized method, the mass ratio of the poly-hydrophilic diaminonaphthalene material (P-HAHQS), carbon black, and polyvinylidene fluoride (PVDF) is (7-7.3): (1.8-2): (0.8-1.2); the mass loading of the poly-hydrophilic diaminonaphthalene material (P-HAHQS) on the cathode electrode is (0.2-1) mg cm -2 .
[0015] More optimally, in step S2, the drying temperature is 80-85°C, and the drying time is 10-12 hours.
[0016] More optimally, the compaction density of the cathode electrode is 2 g / cc.
[0017] More optimally, the electrolyte includes lithium trifluoromethanesulfonate (LiCF3SO3) and lithium hexafluorophosphate (LiPF6) in a volume ratio of 1:1; the concentration of the electrolyte is 0.5 mol / L.
[0018] Preferably, the anode and cathode plates have an area of 1 to 1.54 cm -2 .
[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention mixes diaminonaphthalene with concentrated nitric acid solution and performs an oil bath heating reaction, which will be beneficial to expand the pore spacing of diaminonaphthalene molecules, increase more reaction sites and increase its hydrophilicity. Subsequently, the hydrophilic diaminonaphthalene (HAHQS) electrode is electropolymerized by electrochemical polymerization with the charging voltage as the cutoff condition, so that diaminonaphthalene (AHQS) undergoes self-polymerization to form a corresponding large conjugated framework, increase more active sites and a larger molecular structure and molecular layer spacing, and finally obtain a poly-hydrophilic diaminonaphthalene (P-HAHQS) cathode material. This allows the finally assembled lithium-ion battery to have a higher specific capacity, excellent rate capability, long-term cycle stability and nearly uniform coulombic efficiency. DETAILED DESCRIPTION
[0020] The following will be combined with the parts by mass in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0021] It should be noted that there is no special restriction on the purchase manufacturers of all raw materials involved in the present invention, and exemplarily include: conductive carbon black: brand Vulcan XC-72 (imported from the United States), purchased from Suzhou Shengernuo Technology Co., Ltd.; diaminonaphthalene, purchased from Sinopharm Chemical Reagent Co., Ltd.; aluminum foil: 12 μm thick, brand H18-1100, purchased from Shenzhen Honglei Metal Materials Co., Ltd.; binder is polytetrafluoroethylene and polyvinylidene fluoride, purchased from Shanghai Huahenghui New Materials Technology Co., Ltd.; battery shell: model CR2032, purchased from Taizhou Yajun Battery Materials Co., Ltd.; diaphragm: polyethylene porous membrane, thickness of 20 μm, purchased from Scientific Resources Pte Ltd; lithium sheet: purchased from Dongguan Liren New Materials Technology Co., Ltd.; gasket: 304 stainless steel disc, purchased from Wuxi Yiri New Materials Technology Co., Ltd.; shrapnel: item number 2032, purchased from Xinghua Benoite Battery Materials Co., Ltd.
[0022] Example 1: A method for preparing an electrochemical polymer material for a lithium ion battery cathode; Step 1: 5 g of diaminonaphthalene (AHQS) was mixed and added into 50 g of 7.6 mol / L concentrated nitric acid, and the mixture was heated in an oil bath at 140°C for 10 hours, filtered and washed with pure water, and vacuum dried at 80°C to obtain hydrophilic diaminonaphthalene (HAHQS); Step 2: Mix 0.9 g of hydrophilic diaminonaphthalene (HAHQS), 0.1 g of polytetrafluoroethylene and pure water, add isopropanol, stir and grind evenly, dry in a vacuum drying oven, and cut into pieces with an area of 1 cm -2 , obtaining hydrophilic diaminonaphthalene (HAHQS) electrode material; Step 3: Construct a three-electrode system and test the electropolymerization of the hydrophilic diaminonaphthalene (HAHQS) electrode material by constant current charging method. During the polymerization process, the cutoff voltage was set to 0.7 V vs. Ag / AgCl and the current density was set to 0.2 A g -1 The electropolymerization reaction time is 2 hours to obtain poly-hydrophilic diaminonaphthalene (P-HAHQS) material; An application of an electrochemical polymer material for a lithium ion battery cathode comprises the following steps: Step S1: 0.7 g of poly-hydrophilic diaminonaphthalene material (P-HAHQS), 0.2 g of Vulcan XC-72 carbon black, 0.1 g of polyvinylidene fluoride (PVDF), and N-methyl-2-pyrrolidone (NMP) were uniformly mixed to prepare a cathode slurry; Step S2: The cathode slurry is coated on aluminum foil, baked at 80°C for 12 hours, rolled, die-cut, slit, tab welded, and rubberized to obtain a cathode electrode sheet; wherein the cathode electrode sheet compaction density is 2 g / cc, and the area of the cathode electrode sheet is 1.54 cm -2 ; Cut the lithium sheet into 1.54 cm -2 As anode electrode; Step S3: (1) the electrolyte includes lithium trifluoromethanesulfonate (LiCF3SO3) and lithium hexafluorophosphate (LiPF6) in a volume ratio of 1:1, and the concentration of the electrolyte is 0.5 mol / L; (2) The cathode electrode and the anode electrode are separated by a polyethylene porous membrane, and the electrolyte is lithium hexafluorophosphate and lithium trifluoromethanesulfonate; these three layers are pressed between two current collectors, one of which is in contact with the cathode electrode and the other is in contact with the anode electrode; the entire lithium-ion battery is placed in an argon-filled glove box and assembled in the order of battery shell, cathode electrode, dripping electrolyte, polyethylene porous membrane, dripping electrolyte, anode electrode, gasket spring, and battery shell to finally form a lithium-ion battery.
[0023] Example 2 is based on Example 1, except that the voltage during the electropolymerization process is set to 0.8 V vs. Ag / AgCl, and the other steps are the same as in Example 1; Step 1: 5 g of diaminonaphthalene (AHQS) was mixed and added into 50 g of 67 wt% concentrated nitric acid, and the mixture was heated in an oil bath at 140° C. for 10 hours, filtered and washed with pure water, and vacuum dried at 80° C. to obtain hydrophilic diaminonaphthalene (HAHQS); Step 2: Mix 0.9 g of hydrophilic diaminonaphthalene (HAHQS), 0.1 g of polytetrafluoroethylene and pure water, add isopropanol, stir and grind evenly, dry in a vacuum drying oven, and cut into pieces with an area of 1 cm -2 , obtaining hydrophilic diaminonaphthalene (HAHQS) electrode material; Step 3: Construct a three-electrode system and test the electropolymerization of the hydrophilic diaminonaphthalene (HAHQS) electrode material by constant current charging method. During the polymerization process, the cutoff voltage was set to 0.8 V vs. Ag / AgCl and the current density was set to 0.2 A g -1 The electropolymerization reaction time is 2 hours to obtain poly-hydrophilic diaminonaphthalene (P-HAHQS) material; An application of an electrochemical polymer material for a lithium ion battery cathode comprises the following steps: Step S1: 0.7 g of poly-hydrophilic diaminonaphthalene material (P-HAHQS), 0.2 g of Vulcan XC-72 carbon black, 0.1 g of polyvinylidene fluoride (PVDF), and N-methyl-2-pyrrolidone (NMP) were uniformly mixed to prepare a cathode slurry; Step S2: The cathode slurry is coated on aluminum foil, baked at 80°C for 12 hours, rolled, die-cut, slit, tab welded, and rubberized to obtain a cathode electrode sheet; wherein the cathode electrode sheet compaction density is 2 g / cc, and the area of the cathode electrode sheet is 1.54 cm -2 ; Cut the lithium sheet into 1.54 cm -2 As anode electrode; Step S3: (1) the electrolyte includes lithium trifluoromethanesulfonate (LiCF3SO3) and lithium hexafluorophosphate (LiPF6) in a volume ratio of 1:1, and the concentration of the electrolyte is 0.5 mol / L; (2) The cathode electrode and the anode electrode are separated by a polyethylene porous membrane, and the electrolyte is lithium hexafluorophosphate and lithium trifluoromethanesulfonate; these three layers are pressed between two current collectors, one of which is in contact with the cathode electrode and the other is in contact with the anode electrode; the entire lithium-ion battery is placed in an argon-filled glove box and assembled in the order of battery shell, cathode electrode, dripping electrolyte, polyethylene porous membrane, dripping electrolyte, anode electrode, gasket spring, and battery shell to finally form a lithium-ion battery.
[0024] Example 3 is based on Example 1, except that the voltage during the electropolymerization process is set to 0.9 V vs. Ag / AgCl, and the other steps are the same as in Example 1; Step 1: 5 g of diaminonaphthalene (AHQS) was mixed and added into 50 g of 67 wt% concentrated nitric acid, and the mixture was heated in an oil bath at 140° C. for 10 hours, filtered and washed with pure water, and vacuum dried at 80° C. to obtain hydrophilic diaminonaphthalene (HAHQS); Step 2: Mix 0.9 g of hydrophilic diaminonaphthalene (HAHQS), 0.1 g of polytetrafluoroethylene and pure water, add isopropanol, stir and grind evenly, dry in a vacuum drying oven, and cut into pieces with an area of 1 cm -2 , obtaining hydrophilic diaminonaphthalene (HAHQS) electrode material; Step 3: Construct a three-electrode system and conduct electropolymerization of the hydrophilic diaminonaphthalene (HAHQS) electrode material by constant current charging method. During the polymerization process, the cutoff voltage was set to 0.9 V vs. Ag / AgCl and the current density was set to 0.2 A g -1 The electropolymerization reaction time is 2 hours to obtain poly-hydrophilic diaminonaphthalene (P-HAHQS) material; An application of an electrochemical polymer material for a lithium ion battery cathode comprises the following steps: Step S1: 0.7 g of poly-hydrophilic diaminonaphthalene material (P-HAHQS), 0.2 g of Vulcan XC-72 carbon black, 0.1 g of polyvinylidene fluoride (PVDF), and N-methyl-2-pyrrolidone (NMP) were uniformly mixed to prepare a cathode slurry; Step S2: The cathode slurry is coated on aluminum foil, baked at 80°C for 12 hours, rolled, die-cut, slit, tab welded, and rubberized to obtain a cathode electrode sheet; wherein the cathode electrode sheet compaction density is 2 g / cc, and the area of the cathode electrode sheet is 1.54 cm -2 ; Cut the lithium sheet to 1.54 cm -2 As anode electrode; Step S3: (1) the electrolyte includes lithium trifluoromethanesulfonate (LiCF3SO3) and lithium hexafluorophosphate (LiPF6) in a volume ratio of 1:1, and the concentration of the electrolyte is 0.5 mol / L; (2) The cathode electrode and the anode electrode are separated by a polyethylene porous membrane, and the electrolyte is lithium hexafluorophosphate and lithium trifluoromethanesulfonate; these three layers are pressed between two current collectors, one of which is in contact with the cathode electrode and the other is in contact with the anode electrode; the entire lithium-ion battery is placed in an argon-filled glove box and assembled in the order of battery shell, cathode electrode, dripping electrolyte, polyethylene porous membrane, dripping electrolyte, anode electrode, gasket spring, and battery shell to finally form a lithium-ion battery.
[0025] Example 4 is based on Example 1, except that the voltage during the electropolymerization process is set to 1 V vs. Ag / AgCl, and the other steps are the same as those in Example 1; Step 1: 5 g of diaminonaphthalene (AHQS) was mixed and added into 50 g of 67 wt% concentrated nitric acid, and the mixture was heated in an oil bath at 140° C. for 10 hours, filtered and washed with pure water, and vacuum dried at 80° C. to obtain hydrophilic diaminonaphthalene (HAHQS); Step 2: Mix 0.9 g of hydrophilic diaminonaphthalene (HAHQS), 0.1 g of polytetrafluoroethylene and pure water, add isopropanol, stir and grind evenly, dry in a vacuum drying oven, and cut into pieces with an area of 1 cm -2 , obtaining hydrophilic diaminonaphthalene (HAHQS) electrode material; Step 3: Construct a three-electrode system and test the hydrophilic diaminonaphthalene (HAHQS) electrode material by constant current charging method. The cutoff voltage during the polymerization process is set to 1 V vs. Ag / AgCl and the current density is set to 0.2 Ag. -1 The electropolymerization reaction time is 2 hours to obtain poly-hydrophilic diaminonaphthalene (P-HAHQS) material; An application of an electrochemical polymer material for a lithium ion battery cathode comprises the following steps: Step S1: 0.7 g of poly-hydrophilic diaminonaphthalene material (P-HAHQS), 0.2 g of Vulcan XC-72 carbon black, 0.1 g of polyvinylidene fluoride (PVDF), and N-methyl-2-pyrrolidone (NMP) were uniformly mixed to prepare a cathode slurry; Step S2: The cathode slurry is coated on aluminum foil, baked at 80°C for 12 hours, rolled, die-cut, slit, tab welded, and rubberized to obtain a cathode electrode sheet; wherein the cathode electrode sheet compaction density is 2 g / cc, and the area of the cathode electrode sheet is 1.54 cm -2 ; Cut the lithium sheet into 1.54 cm -2 As anode electrode; Step S3: (1) the electrolyte includes lithium trifluoromethanesulfonate (LiCF3SO3) and lithium hexafluorophosphate (LiPF6) in a volume ratio of 1:1, and the concentration of the electrolyte is 0.5 mol / L; (2) The cathode electrode and the anode electrode are separated by a polyethylene porous membrane, and the electrolyte is lithium hexafluorophosphate and lithium trifluoromethanesulfonate; these three layers are pressed between two current collectors, one of which is in contact with the cathode electrode and the other is in contact with the anode electrode; the entire lithium-ion battery is placed in an argon-filled glove box and assembled into a lithium-ion battery in the order of battery shell, cathode electrode, dripping electrolyte, diaphragm, dripping electrolyte, anode electrode, gasket spring, and battery shell.
[0026] Example 5 is based on Example 1, the voltage during the electropolymerization process is set to 1.1 V vs. Ag / AgCl, and the other steps are the same as Example 1; Step 1: 5 g of diaminonaphthalene (AHQS) was mixed and added into 50 g of 67 wt% concentrated nitric acid, and the mixture was heated in an oil bath at 140° C. for 10 hours, filtered and washed with pure water, and vacuum dried at 80° C. to obtain hydrophilic diaminonaphthalene (HAHQS); Step 2: Mix 0.9 g of hydrophilic diaminonaphthalene (HAHQS), 0.1 g of polytetrafluoroethylene and pure water, add isopropanol, stir and grind evenly, dry in a vacuum drying oven, and cut into pieces with an area of 1 cm -2 , obtaining hydrophilic diaminonaphthalene (HAHQS) electrode material; Step 3: Construct a three-electrode system and test the electropolymerization of the hydrophilic diaminonaphthalene (HAHQS) electrode material by constant current charging method. During the polymerization process, the cutoff voltage was set to 1.1 V vs. Ag / AgCl and the current density was set to 0.2 A g -1The electropolymerization reaction time is 2 hours to obtain poly-hydrophilic diaminonaphthalene (P-HAHQS) material; An application of an electrochemical polymer material for a lithium ion battery cathode comprises the following steps: Step S1: 0.7 g of poly-hydrophilic diaminonaphthalene material (P-HAHQS), 0.2 g of Vulcan XC-72 carbon black, 0.1 g of polyvinylidene fluoride (PVDF), and N-methyl-2-pyrrolidone (NMP) were uniformly mixed to prepare a cathode slurry; Step S2: The cathode slurry is coated on aluminum foil, baked at 80°C for 12 hours, rolled, die-cut, slit, tab welded, and rubberized to obtain a cathode electrode sheet; wherein the cathode electrode sheet compaction density is 2 g / cc, and the area of the cathode electrode sheet is 1.54 cm -2 ; Cut the lithium sheet into 1.54 cm -2 As anode electrode; Step S3: (1) the electrolyte includes lithium trifluoromethanesulfonate (LiCF3SO3) and lithium hexafluorophosphate (LiPF6) in a volume ratio of 1:1, and the concentration of the electrolyte is 0.5 mol / L; (2) The cathode electrode and the anode electrode are separated by a polyethylene porous membrane, and the electrolyte is lithium hexafluorophosphate and lithium trifluoromethanesulfonate; these three layers are pressed between two current collectors, one of which is in contact with the cathode electrode and the other is in contact with the anode electrode; the entire lithium-ion battery is placed in an argon-filled glove box and assembled into a lithium-ion battery in the order of battery shell, cathode electrode, dripping electrolyte, diaphragm, dripping electrolyte, anode electrode, gasket spring, and battery shell.
[0027] Comparative Example 1 is based on Example 1, except that the concentrated nitric acid in step 1 is replaced with acetic acid, and the other steps are the same as those in Example 1; Step 1: 5 g of diaminonaphthalene (AHQS) was mixed and added into 50 g of 67 wt% acetic acid, and the mixture was heated in an oil bath at 140° C. for 10 hours, filtered and washed with pure water, and vacuum dried at 80° C. to obtain hydrophilic diaminonaphthalene (HAHQS); Step 2: Mix 0.9 g of hydrophilic diaminonaphthalene (HAHQS), 0.1 g of polytetrafluoroethylene and pure water, add isopropanol, stir and grind evenly, dry in a vacuum drying oven, and cut into pieces with an area of 1 cm -2 , obtaining hydrophilic diaminonaphthalene (HAHQS) electrode material; Step 3: Construct a three-electrode system and test the electropolymerization of the hydrophilic diaminonaphthalene (HAHQS) electrode material by constant current charging method. During the polymerization process, the cutoff voltage was set to 0.7 V vs. Ag / AgCl and the current density was set to 0.2 A g -1The electropolymerization reaction time is 2 hours to obtain poly-hydrophilic diaminonaphthalene (P-HAHQS) material; An application of an electrochemical polymer material for a lithium ion battery cathode comprises the following steps: Step S1: 0.7 g of poly-hydrophilic diaminonaphthalene material (P-HAHQS), 0.2 g of Vulcan XC-72 carbon black, 0.1 g of polyvinylidene fluoride (PVDF), and N-methyl-2-pyrrolidone (NMP) were uniformly mixed to prepare a cathode slurry; Step S2: The cathode slurry is coated on aluminum foil, baked at 80°C for 12 hours, rolled, die-cut, slit, tab welded, and rubberized to obtain a cathode electrode sheet; wherein the cathode electrode sheet compaction density is 2 g / cc, and the area of the cathode electrode sheet is 1.54 cm -2 ; Cut the lithium sheet to 1.54 cm -2 As anode electrode; Step S3: (1) the electrolyte includes lithium trifluoromethanesulfonate (LiCF3SO3) and lithium hexafluorophosphate (LiPF6) in a volume ratio of 1:1, and the concentration of the electrolyte is 0.5 mol / L; (2) The cathode electrode and the anode electrode are separated by a polyethylene porous membrane, and the electrolyte is lithium hexafluorophosphate and lithium trifluoromethanesulfonate; these three layers are pressed between two current collectors, one of which is in contact with the cathode electrode and the other is in contact with the anode electrode; the entire lithium-ion battery is placed in an argon-filled glove box and assembled into a lithium-ion battery in the order of battery shell, cathode electrode, dripping electrolyte, diaphragm, dripping electrolyte, anode electrode, gasket spring, and battery shell.
[0028] Comparative Example 2 is based on Example 1, except that step 3 is removed and HAHQS electrode material is used as the active material in the cathode material. The other steps are the same as those in Example 1. Step 1: 5 g of diaminonaphthalene (AHQS) was mixed and added into 50 g of 67 wt% concentrated nitric acid, and the mixture was heated in an oil bath at 140° C. for 10 hours, filtered and washed with pure water, and vacuum dried at 80° C. to obtain hydrophilic diaminonaphthalene (HAHQS); Step 2: Mix 0.9 g of hydrophilic diaminonaphthalene (HAHQS), 0.1 g of polytetrafluoroethylene and pure water, add isopropanol, stir and grind evenly, dry in a vacuum drying oven, and cut into pieces with an area of 1 cm -2 , obtaining hydrophilic diaminonaphthalene (HAHQS) electrode material; An application of an electrochemical polymer material for a lithium ion battery cathode comprises the following steps: Step S1: 0.7 g HAHQS electrode material, 0.2 g Vulcan XC-72 carbon black, 0.1 g polyvinylidene fluoride (PVDF), and N-methyl-2-pyrrolidone (NMP) were uniformly mixed to prepare a cathode slurry; Step S2: The cathode slurry is coated on aluminum foil, baked at 80°C for 12 hours, rolled, die-cut, slit, tab welded, and rubberized to obtain a cathode electrode sheet; wherein the cathode electrode sheet compaction density is 2 g / cc, and the area of the cathode electrode sheet is 1.54 cm -2 ; Cut the lithium sheet to 1.54 cm -2 As anode electrode; Step S3: (1) the electrolyte includes lithium trifluoromethanesulfonate (LiCF3SO3) and lithium hexafluorophosphate (LiPF6) in a volume ratio of 1:1, and the concentration of the electrolyte is 0.5 mol / L; (2) The cathode electrode and the anode electrode are separated by a polyethylene porous membrane, and the electrolyte is lithium hexafluorophosphate and lithium trifluoromethanesulfonate; these three layers are pressed between two current collectors, one of which is in contact with the cathode electrode and the other is in contact with the anode electrode; the entire lithium-ion battery is placed in an argon-filled glove box and assembled into a lithium-ion battery in the order of battery shell, cathode electrode, dripping electrolyte, diaphragm, dripping electrolyte, anode electrode, gasket spring, and battery shell.
[0029] Testing: Wuhan Blue Electric Test System (CT3002A) was used to conduct corresponding cycle life test and stability test on button batteries; specific constant current charge and discharge test was adopted, and the cycle life and stability of button batteries were tested at different current densities (0.2, 0.3, 0.5, 2, 4 A g -1 ) for cycle testing, as shown in Table 1, the voltage cutoff range is set to 1.6~3.8V; (1) Cycle life: Start the test equipment and start the constant current charge and discharge test; Charge test: Initially charge the battery at the specified test environment temperature until the specified charge cut-off voltage is reached; Discharge test: Discharge the battery at the specified discharge current until the specified discharge cut-off voltage is reached; Cycle test: Perform multiple charge and discharge cycle tests on the battery according to the above steps; The number of cycles is usually set to 5000, as shown in Table 1; (2) Rate performance: Starting from a low rate, the discharge rate was gradually increased (0.2, 0.3, 0.5, 2, 4 A g-1), and 5 cycles were performed at each rate. The charge and discharge specific capacity at each rate was recorded, as shown in Table 2.
[0030] Table 1
[0031] Conclusion: Compared with Examples 1 to 5, the cycle life of the product obtained in Comparative Example 1 is relatively short and the capacity retention rate is low. This is because compared with the acetic acid solution, the concentrated nitric acid solution selected in the present invention causes a nitration reaction on the surface of diaminonaphthalene, introduces nitro groups, increases the hydrophilicity of diaminonaphthalene, and expands its interlayer spacing, providing a more favorable binding environment for the subsequent electropolymerization reaction of diaminonaphthalene.
[0032] Compared with Comparative Examples 1-2, it can be clearly found that Examples 1-5 have better cycle stability and higher coulombic efficiency; this indicates that the electrochemical polymerization method adopted in the present invention has a significant performance improvement on the material; it is mainly through the gradual growth process of free radical-ion association with free radical-ion; the monomer itself and the polymerization product are converted into intermediates of the polymerization reaction by electrode reaction for polymerization, and finally a polymer material compatible with the cathode of the lithium ion battery is polymerized; the lithium ion battery assembled in this way exhibits excellent electrochemical properties.
[0033] Table 2
[0034] Conclusion: Similar to the conclusion in Table 1, the test results of rate performance also show that the lithium-ion battery assembled with P-AHAQS cathode has better rate performance and faster rate capability.
[0035] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing an electrochemical polymer material for a lithium ion battery cathode, characterized in that: The steps include: Step 1: Add diaminonaphthalene to concentrated nitric acid, mix evenly, heat in an oil bath at high temperature, filter, wash and dry to obtain hydrophilic diaminonaphthalene; Step 2: Evenly mix hydrophilic diaminonaphthalene, polytetrafluoroethylene and pure water, add isopropanol, stir and grind evenly, and dry to obtain a hydrophilic diaminonaphthalene electrode material; Step 3: subjecting the hydrophilic diaminonaphthalene electrode material to an electropolymerization reaction to obtain an electrochemical polymer material.
2. The method for preparing an electrochemical polymer material for a lithium ion battery cathode according to claim 1, characterized in that: In step 3, the parameters of the electropolymerization reaction are set as follows: the charging voltage is set to 0.6~1V vs.Ag / AgCl, and the current density is set to 0.1~0.5 A g -1 The electropolymerization reaction time is 1 to 4 hours; the electrochemical polymerization material is a poly-hydrophilic diaminonaphthalene material.
3. The method for preparing an electrochemical polymer material for a lithium ion battery cathode according to claim 1, characterized in that: In step 2, the mass ratio of the hydrophilic diaminonaphthalene to polytetrafluoroethylene is (9-9.5):(0.5-1); the drying temperature is 60-65° C., and the drying time is 20-24 hours.
4. The method for preparing an electrochemical polymer material for a lithium ion battery cathode according to claim 1, characterized in that: In step 1, the concentration of the concentrated nitric acid is 7.5-8 mol / L; the amount of concentrated nitric acid and pure water used for filtration is 30 times the mass of diaminonaphthalene.
5. The method for preparing an electrochemical polymer material for a lithium ion battery cathode according to claim 1, characterized in that: In step 1, the oil bath heating temperature is 120-140° C., and the oil bath heating time is 12-20 hours; the drying temperature is 80° C., and the drying time is 12-24 hours.
6. An application of an electrochemical polymer material for a lithium ion battery cathode, characterized in that: Application of the electrochemical polymer material obtained by the method for preparing an electrochemical polymer material for a lithium ion battery cathode as claimed in any one of claims 1 to 5 in a lithium ion battery.
7. The use of an electrochemical polymer material for a lithium ion battery cathode according to claim 6, characterized in that: The application method of the electrochemical polymer material in a lithium ion battery is: Step S1: uniformly mixing a poly-hydrophilic diaminonaphthalene material, carbon black, polyvinylidene fluoride, and N-methyl-2-pyrrolidone to prepare a cathode slurry; Step S2: coating the cathode slurry on aluminum foil and drying it, and then rolling, die-cutting, slitting, welding the tabs, and encapsulating it to obtain cathode pole pieces; cutting the lithium sheets into anode pole pieces; Step S3: The cathode electrode and the anode electrode are separated by a polyethylene porous membrane, and an electrolyte of lithium hexafluorophosphate and lithium trifluoromethanesulfonate is used; the three layers are pressed between two collectors, one of which is in contact with the cathode electrode and the other is in contact with the anode electrode; the entire lithium-ion battery is in a glove box filled with argon.
8. The use of an electrochemical polymer material for a lithium ion battery cathode according to claim 7, characterized in that: The mass ratio of the poly-hydrophilic diaminonaphthalene material, carbon black and polyvinylidene fluoride is (7-7.3):(1.8-2):(0.8-1.2); the mass loading of the poly-hydrophilic diaminonaphthalene material on the cathode electrode is (0.2-1) mg cm -2 .
9. The use of an electrochemical polymer material for a lithium ion battery cathode according to claim 7, characterized in that: In step S2, the drying temperature is 80-85°C, and the drying time is 10-12 hours.